2007
DOI: 10.1080/00207140701673118
|View full text |Cite
|
Sign up to set email alerts
|

Responding and Failing to Respond to Both Hypnosis and a Kinesthetic Illusion, Chevreul's Pendulum

Abstract: In this study, participants who failed to exhibit pendulum movement in response to Chevreul's Pendulum (CP) instructions had lower Stanford Hypnotic Susceptibility Scale, Form A (SHSS:A) scores and reported experiencing less subjective response to hypnosis than did their counterparts who exhibited CP movement. However, intensity scores on Shor's Personal Experiences Questionnaire (PEQ) did not differ between pass- and fail-CP groups. Additionally, pass-CP participants showed positive correlations between PEQ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Those assigned to the hypnosis intervention were administered the Harvard Group Scale of Hypnotic Susceptibility to track whether symptom improvement is associated with hypnotizability (Iglesias & Iglesias, 2008;Lichtenberg, Shapira, Kalish, & Abramowitz, 2009;Nash et al, 2009;Oneal, Patterson, Soltani, Teeley, & Jensen, 2008;Pyun & Kim, 2008;Raz, 2008;Wagstaff, Cole, & Brunas-Wagstaff, 2008;Whitehead, Noller, & Sheehan, 2008;Xu & Cardeña, 2008;Yard, DuHamel, & Galynker, 2008). The authors include a host of measures to detect changes in cognition and coping strategies sometimes associated with hypnotic interventions (Karlin, Hill, & Messer, 2008;Nathanson, 2009;Pekala et al, 2008;Pyun & Kim, 2009;Robertson, 2009aRobertson, , 2009bSala et al, 2008;Szendi et al, 2009;Tschugguel & Hunter, 2008). Standardized scales as well as pain diaries were used at baseline and during three treatment phase intervals.…”
Section: Journal: Health Psychologymentioning
confidence: 99%
“…Those assigned to the hypnosis intervention were administered the Harvard Group Scale of Hypnotic Susceptibility to track whether symptom improvement is associated with hypnotizability (Iglesias & Iglesias, 2008;Lichtenberg, Shapira, Kalish, & Abramowitz, 2009;Nash et al, 2009;Oneal, Patterson, Soltani, Teeley, & Jensen, 2008;Pyun & Kim, 2008;Raz, 2008;Wagstaff, Cole, & Brunas-Wagstaff, 2008;Whitehead, Noller, & Sheehan, 2008;Xu & Cardeña, 2008;Yard, DuHamel, & Galynker, 2008). The authors include a host of measures to detect changes in cognition and coping strategies sometimes associated with hypnotic interventions (Karlin, Hill, & Messer, 2008;Nathanson, 2009;Pekala et al, 2008;Pyun & Kim, 2009;Robertson, 2009aRobertson, , 2009bSala et al, 2008;Szendi et al, 2009;Tschugguel & Hunter, 2008). Standardized scales as well as pain diaries were used at baseline and during three treatment phase intervals.…”
Section: Journal: Health Psychologymentioning
confidence: 99%
“…They also confirmed that restraining the arm at the wrist decreased the pendulum oscillation and demonstrated that out of 75 subjects, only 60 were able to create the illusion (Easton and Shor, 1976). Hypnosis research uses Chevreul's pendulum illusion as a tool for testing a patient's response to the technique, with patients that are not able to move the pendulum generally being unresponsive to hypnosis (Karlin et al, 2007).…”
Section: Introductionmentioning
confidence: 84%
“…Like an IQ test, the participant had to be willing enough to try to do each task in order for measurement to be valid, but willingness acted as a gatekeeper of, rather than reason for, hypnotizability scores (cf. Karlin, Hill, & Messer, 2005).…”
Section: Hypnosis and The Evidence Base For Evidence-based Psychothementioning
confidence: 99%